2008
DOI: 10.1007/s10499-008-9200-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of food thermal treatment on growth, absorption, and assimilation efficiency of juvenile cuttlefish, Sepia officinalis

Abstract: The diet of frozen grass shrimp (P. varians) was compared to similar grass shrimp that had suffered either boiling, drying at 60°C, or freeze-drying by lyophilization at -40°C. In experiment 1, cuttlefish fed the frozen shrimp were significantly larger (P \ 0.05) at the end of 10 days and at the end of the experiment, compared with those fed the boiled or dried shrimp. Growth rates were also higher for cuttlefish fed the frozen shrimp, compared with the remaining two. Growth rates were also higher for cuttlefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…Domingues et al . () reported similar results when feeding cooked or raw shrimp to S. officinalis . Present results also confirm that lyophilized crab with native protein alone and combined with lyophilized squid covered the nutritional requirements of O. maya , producing acceptable growth rates.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Domingues et al . () reported similar results when feeding cooked or raw shrimp to S. officinalis . Present results also confirm that lyophilized crab with native protein alone and combined with lyophilized squid covered the nutritional requirements of O. maya , producing acceptable growth rates.…”
Section: Discussionmentioning
confidence: 62%
“…There are evidences that demonstrate that meat cooking affected myofibrillar protein susceptibility to proteases, reducing the meat digestibility (Santé‐Lhoutellier, Astruct, Marinova, Greve & Gatellier ; Domingues et al . ; Gatellier & Santé‐Lhoutellier ). Another possible explanation is related to ingredient condition during food elaboration.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the present study results are not that conclusive, since no differences were detected in growth after 56 days. Domingues et al (2009) reported better growth and survival performance in S. officinalis, when lower temperature processing of shrimp was applied. In that study, the best results were with freeze-dried (− 40°C), instead of dried (60°C) or boiled (100°C) shrimp.…”
Section: Discussionmentioning
confidence: 94%
“…In this sense, various raw materials -other cephalopods Morillo-Velarde et al, 2012), fish (Estefanell et al, 2013; and crustacean species (Cerezo Valverde et al, 2008;Estefanell et al, 2013;Querol et al, 2014a); bindersalginate (Cerezo Valverde et al, 2008; and gelatin (Cerezo Valverde et al, 2008;Estefanell et al, 2013;; and raw material preparation -fresh (Cerezo Valverde et al, 2008); dried (Estefanell et al, 2013;Querol et al, 2013) or freezedried (Morillo-Velarde et al, 2012), were recently evaluated. However, results regarding the effects of thermal treatment applied to natural food for cuttlefish (Domingues et al, 2009) should not be overlooked because commercial meals are normally processed applying high temperature (≈100°C). Indeed, the latter has led Rosas et al (2013) to perform specific experiments related to changes in protein structure during cooking (which affects protein digestibility) and by alterations on nutritional characteristics during ingredient process (which affects the nutritional composition of diets).…”
Section: Introductionmentioning
confidence: 99%
“…The European cuttlefish S. officinalis has been maintained, reared, and cultured in the laboratory for many years (Boletzky 1975(Boletzky , 1979(Boletzky , 1983Richard 1971Richard , 1975Pascual 1978;Boletzky and Hanlon 1983;Forsythe et al 1991Forsythe et al , 1994Lee et al 1991;Domingues 1999;Domingues et al 2001Domingues et al , 2002Domingues et al , 2006Domingues et al , 2008b. It is highly adaptable to life in captivity, has large eggs, a high hatchling survival, and sedentary behavior, tolerates high culture densities and handling, presents little cannibalism, accepts dead prey (Forsythe et al 1994) and, most importantly, readily reproduces in captivity (Domingues et al 2002(Domingues et al , 2003a(Domingues et al , 2006.…”
Section: Introductionmentioning
confidence: 99%